2015
DOI: 10.1063/1.4933369
|View full text |Cite
|
Sign up to set email alerts
|

Opening the way to molecular cycloaddition of large molecules on supported silicene

Abstract: Within density functional theory, the adsorption of the H2Pc molecule on the (3 × 3) silicene/(4 × 4) Ag(111) surface has been investigated. We observe an electronic redistribution in the central macrocycle of the H2Pc molecule and the formation of two Si - N covalent bonds between the molecule and the silicene, in agreement with a cycloaddition reaction. However, while on SiC(0001)(3 × 3) or Si(111)(√3×√3)R30°-boron, the H2Pc molecule remains planar, and the H2Pc molecule takes a butterfly conformation on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…Figure 3(f) presents the electron localization function (ELF) for one molecule on germanene/Al(1 1 1). The ELF has already been successfully used in order to characterize interactions in similar systems [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 3(f) presents the electron localization function (ELF) for one molecule on germanene/Al(1 1 1). The ELF has already been successfully used in order to characterize interactions in similar systems [60,61].…”
Section: Resultsmentioning
confidence: 99%
“…Xenes functionalized by large planar molecules have been studied too. For example, phthalocyanine (H 2 Pc) was predicted to interact weakly with silicene/Ag(1 1 1) system [197]. Its family member, iron phthalocyanine (FePc) has been deposited on silicene/ZrB 2 and was shown to remain stable up to room temperature at the same time retaining its electronic states [198].…”
Section: Adsorption Of Moleculesmentioning
confidence: 99%
“…In addition, Stephan et al investigated the adsorption characteristics of H 2 Pc molecule on silicene above Ag (111). 105 They showed that, due to an electostatic or polarization repulsion between H 2 Pc molecule and Si surface, H 2 Pc molecule adopts a butterfly configuration on this surface. However, this molecule shows a planar configuration on the SiC and SiB surfaces.…”
Section: Functionalization Via Organic Molecule Adsorptionmentioning
confidence: 99%